Does Military Spending Nonlinearly Affect Economic Growth in South Africa?. Issue 4 (7th June 2019) - Phiri, Andrew
Abstract: Using annual data collected from 1988 to 2015, this study provides evidence of a non-linear relationship between military spending, economic growth and other growth determinants for the South African economy. The empirical study is based on estimates of a logistic smooth transition regression (LSTR) model and our empirical results point to an inverted U-shaped relationship between military spending and economic growth for the data. Furthermore, our empirical results suggest that the current levels of military spending, as a component of total government expenditure, are too high in the South African economy and need to be transferred towards more productive non-military expenditure in order to improve the performance of economic growth and other growth determinants.